Dementia prevalence and incidence among the Indigenous and non‐Indigenous populations of the Northern Territory. Issue 8 (5th May 2014) - Li, Shu Qin; Guthridge, Steven L; Eswara Aratchige, Padmasiri; Lowe, Michael P; Wang, Zhiqiang; Zhao, Yuejen; Krause, Vicki
Abstract: Objective : To estimate the prevalence and incidence of dementia in Northern Territory Indigenous and non‐Indigenous populations. Design, setting and participants: Four data sources were used to identify clients with a diagnosis of dementia, from 1 January 2008 to 31 December 2011. The data sources included hospital admissions, aged care services, primary care and death registration. A capture–recapture method was used to estimate prevalence and incidence, including both diagnosed and unknown cases. Main outcome measures: Prevalence and incidence of dementia among the NT Indigenous and non‐Indigenous populations. Results: In 2011, the estimated prevalence in the NT Indigenous population aged 45 years and over was 3.7 per 100, and 1.1 per 100 in the corresponding NT non‐Indigenous population. The age‐adjusted prevalence for the NT Indigenous population was 6.5 per 100, compared with the NT non‐Indigenous prevalence of 2.6 per 100, which was similar to the national rate. The prevalence rate ratios of NT Indigenous to NT non‐Indigenous men and women, respectively, were: 6.5 and 5.5 for the 45–64‐years age group, 4.0 and 4.1 for those aged 65–74 years and 2.1 and 1.9 for those aged 75 years and over. The age‐adjusted incidence among the NT Indigenous population aged 45 years and over (27.3 per 1000 person‐years) was higher than that among the NT non‐Indigenous population (10.7 per 1000 person‐years). Conclusion: The NT Indigenous population has a much higher prevalence and incidence of dementia and younger onset of disease compared with their non‐Indigenous counterparts. The results highlight the urgent need for interventions to moderate the emerging impact of dementia in the Australian Indigenous population.